2017
DOI: 10.1007/s11745-017-4300-z
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Inhibits Oxygen Consumption Rate Independent of Alteration in Cardiolipin Levels in H9c2 Cells

Abstract: Small clinical studies have shown that oral treatment with the plant alkaloid berberine (BBR) reduces blood glucose levels similar to that of metformin and have promoted its use as a novel anti‐diabetic therapy. However, in vitro studies have shown that high concentrations of BBR potently inhibit cell proliferation through inhibition of mitochondrial function. Cardiolipin (Ptd2Gro) is a key phospholipid required for regulating mitochondrial bioenergetic function. We examined if BBR inhibited oxygen consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In addition, berberine protected cardiomyocytes from HG-induced damage and ischemia-reperfusion via enhancement of AMPK [116,120,124,132], PPARα [115] and PI3K-Akt-eNOS anti-apoptotic signaling pathways [116]. Berberine also attenuated cardiac fibrosis, possibly by reducing insulinlike growth factor (IGF)-1 receptor expression in cardiac fibroblasts [129], and enhanced lipid metabolism in cardiomyocytes, possibly via protein kinase C inhibition [119,127]; it also suppressed cardiac arrhythmia by modulating K + and Ca 2+ [110,113]. Furthermore, berberine may alleviate vascular dysfunction in diabetes by acting on adipose tissues.…”
Section: Vascular Dysfunctionmentioning
confidence: 99%
“…In addition, berberine protected cardiomyocytes from HG-induced damage and ischemia-reperfusion via enhancement of AMPK [116,120,124,132], PPARα [115] and PI3K-Akt-eNOS anti-apoptotic signaling pathways [116]. Berberine also attenuated cardiac fibrosis, possibly by reducing insulinlike growth factor (IGF)-1 receptor expression in cardiac fibroblasts [129], and enhanced lipid metabolism in cardiomyocytes, possibly via protein kinase C inhibition [119,127]; it also suppressed cardiac arrhythmia by modulating K + and Ca 2+ [110,113]. Furthermore, berberine may alleviate vascular dysfunction in diabetes by acting on adipose tissues.…”
Section: Vascular Dysfunctionmentioning
confidence: 99%
“…In addition, we found that BBR could enhance the expression of iPLA 2 β in MIN6 mitochondria. Chang et al have observed that BBR can increase CL levels in H9C2 cells 19. Given these results, we hypothesized that BBR could inhibit beta-cell apoptosis by enhancing the iPLA 2 β/CL/Opa1 pathway.…”
Section: Introductionmentioning
confidence: 80%
“…For Blue-Native polyacrylamide gel electrophoresis (BN-PAGE) analysis, mitochondrial protein (80 µg) was treated with 0.2% digitonin and then separated on a 3-12% gradient gel as described [9]. Immunoblot analysis of the gel was performed using anti-PKCδ antibody (1:1000) (Abcam, Toronto, ON, Canada) as described [17]. PKCδ was visualized using the Amersham Enhanced Chemiluminescence Western blotting detection system (VWR, was not certified by peer review) is the author/funder.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblot analysis of the gel was performed using anti-PKCδ antibody (1:1000) (Abcam, Toronto, ON, Canada) as described [17]. PKCδ was visualized using the Amersham Enhanced Chemiluminescence Western blotting detection system (VWR, Mississauga, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%